Preparation and characterization of chitosan grafted PMMA via gamma radiation for electrolyte in supercapacitor / Nor Kartini Jaafar - Jaafar, Nor Kartini (2018)
Solid polymer electrolytes may generally be defined as membranes that possess transport properties comparable with that of common liquid ionic solutions. In the present study, Chitosan (Ch), methyl methacrylate (MMA) were used to produce a grafted polymer Chg- PMMA using gamma irradiation grafting method. The grafted polymer Ch-g-PMMA, lithium triflouromethanesulfate (LiCF3S03 or LiTf), ethylene carbonate (EC) and silicon dioxide (SiCh) were then used in the preparation of solid polymer electrolytes (SPE), gel polymer electrolyte (GPE) and composite polymer electrolyte (CPE). All samples were prepared by solution cast technique. Physical and electrical properties of SPE, GPE and CPE were investigated to find the suitable grafted polymer electrolytes composition for fabrication in lithium polymer supercapacitor. The conductivity of all samples was calculated from the complex impedance plot in the frequency range 100 Hz to 1 MHz…